Determinasi Harga Saham dari Rasio Likuiditas, Rasio Profitabilitas dan Nilai Buku pada Perusahaan Sektor Makanan & Minuman Yang Terdaftar di Bursa Efek Indonesia - Muhammad Berliandy Heikel; Aang Syahdina (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2024)
Stock price fluctuations are often influenced by a company's fundamental factors, such as liquidity, profitability, and book value. In the food and beverage subsector, which experienced rapid growth during the pandemic, it is crucial to evaluate how these financial ratios impact stock prices to understand the company’s performance in the capital market. This study aims to examine the effect of liquidity, profitability, and book value ratios on stock prices of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. Using purposive sampling with 110 samples, the data were analyzed quantitatively through multiple regression using EViews 13.0. The results show that the Current Ratio (CR) and Return on Assets (ROA) have no significant effect on stock prices, while the Price to Book Value (PBV) has a positive effect. Simultaneously, CR, ROA, and PBV have an impact on stock prices.